Research on the Cultivation of Cross-cultural Awareness in English Translation Teaching Based on Computer Multimedia Technology. Issue 2 (October 2020) - Meng, Cong
Abstract: With the continuous development of the times, the importance of education is gradually highlighted. English is the second language most Chinese students learn. In the process of learning, students can not only grasp some basic theoretical knowledge, but also constantly cultivate students' cross-cultural awareness. Through the cultivation of cross-cultural awareness, students can better understand the content of foreign culture and language. At present, many colleges and universities have carried out college English translation teaching based on computer multimedia technology. By comparing and interpreting the cultures of the two countries, the students deepen their impression of foreign cultures and constantly improve their English level, which promotes their better development.